Persistent post-traumatic headache in a pediatric patient with cerebral venous thrombosis: a case report - Jomaa , Assia Jihad; Coelho, Ana Francisca de Barros; Iachinski , Renato Endler; Zenatti , Gabriel Angelo Garute; Neto , Ivo Marcos Darella Lorenzin Fernandes (Headache Medicine, 2024)
Introduction: The most common symptom of post-traumatic headache (PTH) is a significant overlap with the symptoms of migraine or tension-type headache. The clinical of cerebral venous thrombosis (CVT) includes isolated headache or increased intracranial pressure, focal neurological presentations, subacute encephalopathy and cavernous sinus syndrome with multiple cranial neuropathies. CVT resulting from TBI processes in pediatrics is considered rare. Only 4% of the cases with TVC are associated with TBI. Objective: This presentation aims to demonstrate an atypical case of CVT following TBI in a pediatric patient, associated with persistent headaches. Therefore, discusses the importance of an early differential diagnosis between PTH and headache related to CVT in order to reduce the risk of unfavorable outcomes.  Case presentation: Male, 5 years, manifesting persistent headache 48 hours after the TBI to the occipital region. In addition, on neurological admission he presented with inconsolable crying and 2 episodes of emesis, not preceded by nausea. Physical examination showed no focal deficits. A non-contrasted computed tomography (CT) scan of the skull was performed to better investigate the condition, which revealed a diastasis of the occipitomastoid suture on the left, with no other alterations. Was discharged with symptomatic treatment and monitored. After 48 hours, he was readmitted to the service due to a new sudden episode of headache, associated with episodes of emesis. A new skull CT scan showed hyperdensity in the region of the left transverse sinus. Was followed up with venous angiography of the skull, which showed a failure of the flow signal in the left transverse and sigmoid sinus, extending to the distal internal jugular vein, compatible with cerebral venous thrombosis. After diagnosis, full anticoagulation and strict neurological observation were initiated. Discharged without any neurological deficits and complete resolution.Conclusion: This is an atypical case in pediatric patient of persistent PTH related to CVT. Treatment of the condition must be individualized according to each case. Currently, there are no specific guidelines on therapeutic resources for resolving cases of persistent headache related to trauma.